POLITIK HUKUM PEMERINTAH TERHADAP KEBIJAKAN REMISI - Supriyedi Syamsuri (SOL JUSTICIA, 2021)
Abstract: Law refers to a rule of life that is in accordance with the ideals of living together and the rules of justice. The content of the rule of law should be fair. Without justice, the law is only formalized violence. Law is felt to be important when dealing with injustice. People sue the actual Court to demand justice. Law is basically a whole of the rules and all the principles that regulate the social life in society and aims to maintain order, and includes various institutions and processes for the application of the rules as a reality in society. The approach in this research is the library research approach. This research will be conducted at the Regional Library of South Sumatra and Universities in the South Sumatra Region which is the object and main focus of researchers in viewing and analyzing the Government's Legal Politics on Remission Policy. Keywords : Politics of Law, Policy, and Remission.